Epidemiology of COVID-19 infection in young children under five years: A systematic review and meta-analysis. Issue 4 (22nd January 2021) - Bhuiyan, Mejbah Uddin; Stiboy, Eunice; Hassan, Md. Zakiul; Chan, Mei; Islam, Md. Saiful; Haider, Najmul; Jaffe, Adam; Homaira, Nusrat
Abstract: Introduction: Emerging evidence suggests young children are at greater risk of COVID-19 infection than initially predicted. However, a comprehensive understanding of epidemiology of COVID-19 infection in young children under five years, the most at-risk age-group for respiratory infections, remain unclear. We conducted a systematic review and meta -analysis of epidemiological and clinical characteristics of COVID-19 infection in children under five years. Method: Following the Preferred Reporting Items for Systematic Reviews and Meta-analyses, we searched several electronic databases (Pubmed, EMBASE, Web of Science, and Scopus) with no language restriction for published epidemiological studies and case-reports reporting laboratory-confirmed COVID-19 infection in children under five years until June 4, 2020. We assessed pooled prevalence for key demographics and clinical characteristics using Freeman-Tukey double arcsine random-effects model for studies except case-reports. We evaluated risk of bias separately for case-reports and other studies. Results: We identified 1, 964 articles, of which, 65 articles were eligible for systematic review that represented 1, 214 children younger than five years with laboratory-confirmed COVID-19 infection. The pooled estimates showed that 50% young COVID-19 cases were infants (95% CI: 36% − 63%, 27 studies); 53% were male (95% CI: 41% − 65%, 24 studies); 43% were asymptomatic (95% CI: 15% − 73%, 9 studies) and 7% (95% CI: 0% − 30%, 5 studies) had severe disease that required intensive-care-unit admission. Of 139 newborns from COVID-19 infected mothers, five (3.6%) were COVID-19 positive. There was only one death recorded. Discussion: This systematic review reports the largest number of children younger than five years with COVID-19 infection till date. Our meta -analysis shows nearly half of young COVID-19 cases were asymptomatic and half were infants, highlighting the need for ongoing surveillance to better understand the epidemiology, clinical pattern, and transmission of COVID-19 to develop effective preventive strategies against COVID-19 disease in young paediatric population.